2018
DOI: 10.1038/s41598-018-28709-y
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule inhibition of RAS/MAPK signaling ameliorates developmental pathologies of Kabuki Syndrome

Abstract: Kabuki Syndrome (KS) is a rare disorder characterized by distinctive facial features, short stature, skeletal abnormalities, and neurodevelopmental deficits. Previously, we showed that loss of function of RAP1A, a RAF1 regulator, can activate the RAS/MAPK pathway and cause KS, an observation recapitulated in other genetic models of the disorder. These data suggested that suppression of this signaling cascade might be of therapeutic benefit for some features of KS. To pursue this possibility, we performed a foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 50 publications
(58 reference statements)
1
28
0
Order By: Relevance
“…Among them are RASopathies, which include the Noonan, Costello and cardio-facio-cutaneous (CFC) syndromes [103, 104], extracranial arteriovenous malformation [105], and Kabuki syndrome [106]. These last disorders can be induced by activating the mutation of MEK (CFC) or upstream components of the ERK1/2 cascade [107].…”
Section: Mapk Cascades In Diseasementioning
confidence: 99%
“…Among them are RASopathies, which include the Noonan, Costello and cardio-facio-cutaneous (CFC) syndromes [103, 104], extracranial arteriovenous malformation [105], and Kabuki syndrome [106]. These last disorders can be induced by activating the mutation of MEK (CFC) or upstream components of the ERK1/2 cascade [107].…”
Section: Mapk Cascades In Diseasementioning
confidence: 99%
“…A recent study revealed a link between RAS/MAPK pathway hyperactivation and the neurological and craniofacial defects in the context of KS knockdown in zebrafish (28). In line with this, chemical inhibition of a downstream target of this pathway (BRAF inhibitor), partially rescued the craniofacial and neuroanatomical phenotype of kmt2ddepleted zebrafish larvae in transient knockdown and kmt2d +/heterozygous crosses (29). These findings suggest a pathway involved in some aspects of KS-neurological defects and establishes the utility of zebrafish for drugs screening in KS.…”
Section: Introductionmentioning
confidence: 72%
“…We focused on three different genes ( anln, kmt2d , and smchd1 ) for which (a) we have substantial experience in this model organism and (b) which give reproducible, quantitative defects in kidney morphogenesis (Hall et al, 2018), mandibular and neuronal development (Tsai et al, 2018), and craniofacial morphogenesis (Shaw et al, 2017). For each locus, we used sgRNAs that had the following three characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…For each locus, we used sgRNAs that had the following three characteristics. First, for each of the three genes, we selected an sgRNA with demonstrated high efficiency (100%) and an sgRNA with low efficiency (∼30%), as determined by heteroduplex analysis and Sanger sequencing of cloned PCR products (Hall et al, 2018; Shaw et al, 2017; Tsai et al, 2018) (Suppl. Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation